2017
DOI: 10.1021/acsnano.7b05664
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Structure with Nano-Heterogeneity Promotes Cationic Transport in Concentrated Electrolytes

Abstract: Using molecular dynamics simulations, small-angle neutron scattering, and a variety of spectroscopic techniques, we evaluated the ion solvation and transport behaviors in aqueous electrolytes containing bis(trifluoromethanesulfonyl)imide. We discovered that, at high salt concentrations (from 10 to 21 mol/kg), a disproportion of cation solvation occurs, leading to a liquid structure of heterogeneous domains with a characteristic length scale of 1 to 2 nm. This unusual nano-heterogeneity effectively decouples ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

83
624
6

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 353 publications
(713 citation statements)
references
References 58 publications
83
624
6
Order By: Relevance
“…The lower ability of the polymer chain to form a stable complex‐like structure should provide a cation‐dominated conduction in SPEs. In addition, Suo, Borodin, and coworkers, have reported that highly concentrated 1,3‐dioxolane (DOL)‐dimethoxyethane (DME)/LiTFSI electrolytes and H 2 O/LiTFSI aqueous electrolytes have high t + values. A situation similar to the PEC electrolyte may have occurred in these highly concentrated liquid electrolytes.…”
Section: Resultsmentioning
confidence: 99%
“…The lower ability of the polymer chain to form a stable complex‐like structure should provide a cation‐dominated conduction in SPEs. In addition, Suo, Borodin, and coworkers, have reported that highly concentrated 1,3‐dioxolane (DOL)‐dimethoxyethane (DME)/LiTFSI electrolytes and H 2 O/LiTFSI aqueous electrolytes have high t + values. A situation similar to the PEC electrolyte may have occurred in these highly concentrated liquid electrolytes.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, the water molecules and lithium ions simultaneously increased on the surface of the negative electrode interface layer. In this case, almost all of water molecules were strongly coordinated to lithium ions, resulting in the remarkably reduced water activities near negative electrode ,. Therefore, the EDLC using 21 m WIS electrolyte could completely reach a high operation voltage of 2.2 V.…”
Section: Resultsmentioning
confidence: 95%
“…Recently, Wang et.al showed that the water‐in‐salt (WIS) electrolyte based on lithium bis(trifluoromethanesulfonyl) imide (LiTFSI) and water system with concentration above 20 m (mol kg −1 ) exhibits a wide stability window of 3.0 V on stainless steel gird electrodes . This wide stability window is attributed to the forming special shell structure in the electrolyte, in which the water molecules are strongly coordinated to the lithium ions, resulting the passivation of water activities . The special structure also brings up the problem about ionic conductivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dynamic behavior in liquid electrolytes can be treated with molecular dynamics (MD) simulations, which provide insight into solution structures, transport mechanisms, and electrolyte decomposition pathways . With the help of supercomputers, a system consisting of up to 400–500 atoms can be simulated with first principles MD simulations with a plane wave basis set and pseudopotential method.…”
Section: Introductionmentioning
confidence: 99%